2017
DOI: 10.3390/vetsci4030038
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Allergens from Furred Mammals: Environmental and Occupational Exposure

Abstract: Furry mammals kept as pets, farm and laboratory animals are important allergen sources. The prevalence of sensitization to furred mammals appears to be increasing worldwide. Several mammalian allergens from diverse species are well characterized with regard to their molecular structure and immunogenicity, and some are already available for component-resolved allergy diagnostics. The distribution of various mammalian allergens has been extensively studied during the past few decades. Animal allergens were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 104 publications
1
42
0
3
Order By: Relevance
“…The exposure to biocontaminants is well documented and studied in several occupational settings, and few data are available in animal facilities, although more attention has been addressed to animal allergens. These biological agents are aeroallergens, mainly lipocalins, derived by different biological fluids and/or tissue (saliva, serum, urine, dander, hair, fur) that remain in suspension for different times in relation to meteorological conditions and factors influencing their dispersion [1,2]. In recent years, the topic regarding animal allergen exposure has been treated both in pets [3][4][5] and experimental animals [6][7][8][9], and attention has been also addressed to co-exposure of allergens and endotoxins in these workplaces, although in a more restricted way [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to biocontaminants is well documented and studied in several occupational settings, and few data are available in animal facilities, although more attention has been addressed to animal allergens. These biological agents are aeroallergens, mainly lipocalins, derived by different biological fluids and/or tissue (saliva, serum, urine, dander, hair, fur) that remain in suspension for different times in relation to meteorological conditions and factors influencing their dispersion [1,2]. In recent years, the topic regarding animal allergen exposure has been treated both in pets [3][4][5] and experimental animals [6][7][8][9], and attention has been also addressed to co-exposure of allergens and endotoxins in these workplaces, although in a more restricted way [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cats and dogs are the most commonly owned pets; ownership varies around the world, averaging 33% for dogs and 23% cats [21]. Over half of U.S. households have cats or dogs as pets, and their ownership has been increasing over the past decades [22, 23•].…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%
“…In fact, one study showed that “hypoallergenic” dogs had higher Can f 1 levels in hair and coat than “non-hypoallergenic” dog breeds [33]. Truly “hypoallergenic” breeds will be difficult to develop because secretion of cat and dog allergens is not limited to the two major allergens, Fel d 1 and Can f 1 [21, 27, 30]. …”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%
See 2 more Smart Citations